Cardiovascular Effects of Nigella Sativa on Isolated Rabbit Heart and its Impact on Cardiac Remodeling - Abdul Shabbir Ali Bhatti; Aliya Shabbir; Muhammad Kashif Butt; Muhammad Ahmed Bhatti; Muhammad Usman; Abdul Karim (Shalamar Medical & Dental College, Lahore, Pakistan, 2022)
Background: Black Cumin/Nigella sativa (NS) which belongs to the botanical family of Ranunculaceae commonly grows in Eastern Europe, the Middle East, and Western Asia. Its prolonged use can produce physiological changes with or without affecting the architecture of different organs like the heart (cardiac remodeling). The data for the cardiovascular benefits of black cumin are not well-established scientifically. Objectives: To determine the direct cardiovascular effects of Nigella Sativa extract on heart rate, cardiac contractility (apical force), ECG, and coronary flow in the normal heart with and without cardiac remodeling. Methods: This experimental study was conducted on forty-two (42) rabbits. These rabbits were divided into seven groups, each comprising six animals (Group I-VI without cardiac remodeling and Group VII with cardiac remodeling). NS was given to these groups in different doses i.e., Group I (NS=10ug), Group II (NS=30ug), Group III (NS=100ug), Group IV (NS=300ug), Group V (NS=3000ug), Group VI (NS=10000ug) and VII (NS=300ug). Radnoti's working heart system was used to determine the effects of NS on heart rate, cardiac contractility (apical Force), ECG, and coronary flow in a normal heart with and without cardiac remodeling. The results were analyzed using SPSS version 28.   Results: Results of this study revealed negative chronotropic and positive inotropic effects without ECG changes in the normal heart and with ECG changes in the remodeled heart. Conclusions: Prolonged use of Nigella sativa can lead to disturbed ECG by affecting the conducting tissue.